Effects of Fe2O3 on Reduction Process of Cr-Containing Solid Waste Self-Reduction Briquette and Relevant Mechanism - Tuo Wu; Yanling Zhang; Zheng Zhao; Fang Yuan (Metals, 2019)
High-temperature quench method, scanning electron microscope-energy dispersive spectroscopy (SEM-EDS), and thermodynamic analysis were adopted to study the effects of Fe2O3 on reduction process of Cr-containing solid waste self-reduction briquette (Cr-RB). Moreover, the relevant mechanism was also studied. The results clearly showed that the addition of Fe2O3 decreased the chromium-iron ratio (Cr/(Fe + Cr)) of Cr-RB itself and promoted the reduction of chrome oxide in the Cr-containing solid wastes such as stainless steel slag and dust. A large number of Fe-C alloy droplets generated in the lower temperature could decrease the activity of reduced chromium by in situ dissolution and the reduction of Cr-oxide was accelerated. Rapid separation of metal and slag could be achieved at a relatively lower temperature, which was very beneficial to the efficient recovery of Cr. Finally, the corresponding mechanism diagram was presented.